La enseñanza del pasado controversial y su impacto en la reconciliación: un estudio de caso en un colegio de élite de Bogotá (2020)
A historical memory education that contributes to reconciliation has the challenge to avoid building closed memory communities, anchored in their own sufferings, and incapable of recognizing the experiences of other social groups in the context of war. Based on a case study in an elite school in Bogotá, this research explores the process of a group of students who learn about the historical memory of the armed conflict and how this contributes to reconciliation processes. The findings suggest that the curriculum proposed by the teacher manages to challenge the students' previous narratives regarding their ways of conceptualizing the difficult history of the conflict and leads them to recognize a wide spectrum of victims. However, aspects related to its dispositions to reconcile with the broad spectrum of armed actors that have participated in the war in Colombia...